Exploring Patient Satisfaction with Nursing Care and its Association with Gender at Tertiary Care Hospital Karachi : Patient Satisfaction with Nursing Care - Rashad, Saqib ur; Bibi, Afsha; Ahmad, Ashfaq; Ahmed, Tufail; Arshad, Zakiya; Ali, Yasir; Ahamd, Hussain; Khaliq, Fazal; Mehboob Ali, Farzana (Pakistan Journal of Health Sciences, 2023)
Patient satisfaction is critical to healthcare quality and significantly impacts patient outcomes and healthcare delivery. Objectives: To explore patient satisfaction with nursing care and its association with gender at a tertiary care Hospital in Karachi, Pakistan. Methods: This cross-sectional Analytical study was conducted at a tertiary care Hospital in Karachi from September 2022 to December 2022. Sixty participants were recruited through a convenient sampling technique from the medical ward. Data were collected through a pretested questionnaire which was reliable. Results: The study found that out of the 60 participants, 3% had a low level of satisfaction, 50% had a moderate level, and 47% had a high level of satisfaction regarding nursing care. Moreover, the study revealed no evidence of an association between gender and level of satisfaction. Conclusions: Based on the findings majority of the participants had a moderate to high level of satisfaction, with only a small percentage reporting low satisfaction. There was no evidence of a relationship between gender and satisfaction level. However, generalizing these findings to a larger population requires more investigation due to the small sample size.